Nietzsche on freedom and autonomy - Gemes, Ken.; May, Simon (Simon Philip Walter) (Oxford : Oxford University Press, 2009)
Nietzsche is a central figure in our modern understanding of the individual as freely determining his or her own values. These essays by leading Nietzsche scholars investigate what this freedom really means.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Liberty; Autonomy (Philosophy)